2017
DOI: 10.1039/c7cp00811b
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of surface energies and water adsorption on Ce-bastnäsite, La-bastnäsite, and calcite via density functional theory and water adsorption calorimetry

Abstract: Rational design of bastnäsite specific collector molecules must exploit its surface structural features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…Periodic-DFT-calculated adsorption energies for SHA, BHA, and SA on bastnäsite-[10 0], the most prevalent bastnäsite surface ( Srinivasan et al, 2017 ; Srinivasan et al., 2016 ), with acidic protons proximal to the adsorbate, are provided in Table 2 , and optimized structures are shown in Figure 1 and detailed in Figure S1 with interactions contributing to adsorption specified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Periodic-DFT-calculated adsorption energies for SHA, BHA, and SA on bastnäsite-[10 0], the most prevalent bastnäsite surface ( Srinivasan et al, 2017 ; Srinivasan et al., 2016 ), with acidic protons proximal to the adsorbate, are provided in Table 2 , and optimized structures are shown in Figure 1 and detailed in Figure S1 with interactions contributing to adsorption specified.…”
Section: Resultsmentioning
confidence: 99%
“…Closer cationic spacing on the calcite surface (d(Ca-Ca) = 4.03 and 4.99 Å) compared with the Ce-bastnäsite surface (d(Ce-Ce) = 4.78 and 7.07 Å) may allow for closer adsorption on the bastnäsite surface and potentially cause differing degrees of strain on the structure of the ligand upon adsorption. Previous work on bastnäsite-collector design highlights variations in cationic spacing in these surfaces ( Srinivasan et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three different methods of calculating interfacial properties via MD simulations were reported by Bahadur et al for liquid–vapor, solid–liquid, and solid–vapor interfaces in the NaCl–water–air system and found that the energy difference method, used here, result in an estimated uncertainty of ±6 mN/m or 7% of the experimental value for the liquid–solid interfacial tension . Additionally, similar methods have been used to calculate the interfacial energy of NaCl–water systems, tricalcium silicate–water, hydroxyapatite–water, and Ce/La–bastnäsite–water systems indicating that this method is well suited for investigation of liquid–solid interfacial tensions in NaCl brine systems . The interaction energies of the last 10 steps of the 1 ns simulation were used to calculate an average liquid–solid interfacial tension along with standard deviation as an error.…”
Section: Methodsmentioning
confidence: 82%
“…Optimizations of this process include the adsorption isotherms of the surfactants, solution pH, zeta potentials of the minerals that make up the ore body, and contact angle measurements . However, with a few notable exceptions, , there is a dearth of fundamental information about the molecular-level structure, reactivity, and reaction mechanisms of the relevant mineral–water interfaces involved in this process. Obtaining this fundamental understanding would allow us to identify the specific surface sites, if any, onto which surfactants bind during complexation and give a confirmed starting structure for rational design of new ligands that are more efficient at causing REE ore minerals to float while simultaneously being more selective for REE ore minerals over gangue.…”
Section: Introductionmentioning
confidence: 99%